Jintai Kyusho, los puntos vulnerables del cuerpo humano - Ibáñez Espinosa, Miguel Ángel (Revista de Artes Marciales Asiáticas, 2012)
Pau Ramon Planellas Vidal. Barcelona: Alas, 2000. 190 Paginas. 17x24 cm. I.S.B.N 84-203-0369-0.